A likely microendemic new species of terrestrial iguana, genus Chalarodon, from Madagascar - Miralles, Aurelien; Glaw, Frank; Ratsoavina, Fanomezana M.; Vences, Miguel (Zootaxa, 2015)
A new species of the hitherto monotypic genus Chalarodon is described from southern Madagascar and a lectotype (ZMB 4360) is designated for C. madagascariensis Peters, 1854. The new species of terrestrial iguana, Chalarodon steinkampi sp. nov., is defined by several morphological characters and by concordant differentiation in mitochondrial and nuclear DNA with >5% uncorrected pairwise genetic distance in the 16S rRNA gene. It can be most clearly recognized by the presence of smooth (vs. keeled) gular and ventral scales, a spotted pattern extending from flanks onto belly, and an unpigmented throat. The new species is known from only a small area between the villages of Amboasary Sud and Esomony, located west of the Andohahela Massif, while C. madagascariensis appears to be widespread over much of southern and western Madagascar. We highlight the need for further exploration of this unprotected region which might host several other microendemic species.